Womens cardiovascular and respiratory system functional state indicators dynamics under influence of swimming classes - Шейко, Лилия (Slobozhanskyi Herald of Science and Sport, 2018)
Liliia Sheiko Purpose: to determine the degree of influence the recreational swimming occupations have on women’s cardiovascular and respiratory systems’ state. Materials & Methods: 52 women of 25–45 years have participated in the research. Data collection was carried out in competitive and recreational swimming groups of the Yu. Bliznuk experimental swimming school at the "Pioneer" swimming pool. Examinees had identical swimming skills. The methods used: questionnaires, testing, instrumental research of the cardiovascular and respiratory systems. The obtained quantitative data was processed using methods of mathematical statistics. Results: the research shows that recreational swimming causes positive changes in the functional state of cardiovascular and respiratory systems of women 25 to 45 years old; the most considerable improvement of cardiovascular and respiratory systems’ indicators is observed after 2 years of occupations. Conclusions: it is established that occupations of recreational swimming for the duration of 2 years have positively affected the state cardiovascular and respiratory systems of women in the age of 25–45.